Work Conditions and Staff Job Commitment: An Empirical Survey of Government-Owned Universities - Adeniji, Adetoun M.; Adelena, Owolabi Paul; Ogunsile, Yetunde O. (Management Research Journal, 2022)
Higher institutions of learning are important to the development of any nation. It becomes imperative to ensure that the work conditions of the staff are conscientiously maintained to ensure job commitment. In view of this, this study investigated work conditions and staff job commitment in Ogun-Owned Universities. The descriptive survey research design was adopted in the study. The sample was made up of 300 staff which was purposively drawn from Olabisi Onabanjo University, Ago-Iwoye and Tai Solarin University of Education, Ijebu-Ode, Ogun State, Nigeria. “Work Conditions and Staff Job Commitment Questionnaire (IWSJCQ)” (r = 0.85) was used for data collection. Mean, standard deviation and Pearson Product Moment Correlation (PPMC) were used to analyze the data collected. Results showed that work conditions is a correlate of job commitment (r = 270, p=0.000 < 0.05). It was recommended that modern work conditions be provided for staff to ensure sustained job commitment.